2022
DOI: 10.1177/19485506221107741
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing the Behavioral-Immune System: The Power of Social Pain

Abstract: People who believe they are invulnerable to infectious diseases often fail to protect themselves against the disease threats that others pose to them. The current paper hypothesizes that social pain—the experience of feeling interpersonally hurt or rejected—can sensitize the behavioral-immune system by giving people added reason to see others as worthy of protecting themselves against. We obtained four daily diary samples involving 2,794 participants who reported how hurt/rejected they felt by those they knew,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The current research adds greater nuance to this point in suggesting that the threat of contagious disease can also sensitize rather than desensitize people to their need for social connection. Consistent with this logic, recent research suggests that people who normally feel invulnerable to infectious disease take daily steps to physically protect themselves against COVID-19 when they have just been hurt by someone close to them, and thus, have reason to question the safety of social connection (S. L. Murray et al, 2022).…”
Section: Strengths and Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The current research adds greater nuance to this point in suggesting that the threat of contagious disease can also sensitize rather than desensitize people to their need for social connection. Consistent with this logic, recent research suggests that people who normally feel invulnerable to infectious disease take daily steps to physically protect themselves against COVID-19 when they have just been hurt by someone close to them, and thus, have reason to question the safety of social connection (S. L. Murray et al, 2022).…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…We used the program mpowsim (http://www.bristol.ac.uk/cmm/ software/mlpowsim/), an add-on program to the MLwiN multilevel modeling software developed by Browne and Golalizadeh (n.d.), to run simulation-based power analyses for our multilevel models. Parameters for this power analysis were drawn from the results of previously published research using similar multilevel models and similar outcome variables (e.g., S. L. Murray et al, 2022), with the added assumption that the conditioning intervention would have no main effect or two-way interactions, but would enter into threeway interactions between daily threat, individual differences in threat vulnerability, and condition with a small effect size of d = .1. The results of this simulation indicated that the proposed model would have an a priori power to reject the null hypothesis of no effect for the three-way interaction of .85 with 500 individual participants measured over 10 time points, and .91 with 600 individual participants measured over 10 time points.…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation
“…We recruited 300 participants from ResearchMatch, a volunteer health‐based online recruitment website that has been used for social psychological research on COVID‐19 (Murray et al, 2022), from January 9th to 21st, 2021 (https://www.researchmatch.org/). After removing 26 participants who either failed or did not respond to an attention check item, 274 participants were left for analysis.…”
Section: Studymentioning
confidence: 99%
“…Given such representational overlay, the model assumes that acute experiences with vulnerability in the physical domain implicitly implicate the potential for safety/harm in the social/relationship domain (and vice versa). For instance, being rejected by close others can accentuate the threat implicit to physical pain ( Eisenberger et al, 2006 ;Kross et al, 2011 ) and contagious diseases ( Murray et al, 2022 ). In contrast, feeling connected to others can attenuate the threat implicit to both physical pain ( Master et al, 2009 ;Eisenberger et al, 2011 ;Wilson and Simpson, 2016 ;Yanagisawa et al, 2011 ) and contagious diseases ( Bressan, 2021 ;Tybur et al, 2020 ).…”
Section: Safer Together: Relationships and Felt Securitymentioning
confidence: 99%